2016
DOI: 10.1177/0971890716637698
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dividend Policy of Indian Companies

Abstract: This article analyzes the trends and the determinants of the dividend policy of Indian companies that were continuously paying dividend during the whole period study that is from 1994–1995 to 2012–2013. We have used the static panel data models to carry out this analysis. From the trend analysis we find that larger, more profitable, more mature and highly liquid firms have higher dividend payout ratio, whereas the firms with high investment opportunity, financial leverage and business risk have lower dividend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 36 publications
12
49
0
8
Order By: Relevance
“…Al-Ajmi and Hussain (2011) and Labhane and Mahakud (2016) show that cash ratio has a positive effect on dividend policy, but Jabbouri (2016) and Khan and Shamim (2017) find a negative effect. Afza and Mirza (2011), Jabbouri (2016), Labhane and Mahakud (2016), and Manneh and Naser (2015) show that debt ratio has a negative relationship with the dividend policy, but Hudiwijono et al (2018) using Indonesian construction companies report a positive effect. Abor and Bokpin (2010), Jabbouri (2016), Kumar et al (2012), and Patra et al (2012) show that asset growth negatively affects dividend policy.…”
Section: Business Perspectivesmentioning
confidence: 99%
“…Al-Ajmi and Hussain (2011) and Labhane and Mahakud (2016) show that cash ratio has a positive effect on dividend policy, but Jabbouri (2016) and Khan and Shamim (2017) find a negative effect. Afza and Mirza (2011), Jabbouri (2016), Labhane and Mahakud (2016), and Manneh and Naser (2015) show that debt ratio has a negative relationship with the dividend policy, but Hudiwijono et al (2018) using Indonesian construction companies report a positive effect. Abor and Bokpin (2010), Jabbouri (2016), Kumar et al (2012), and Patra et al (2012) show that asset growth negatively affects dividend policy.…”
Section: Business Perspectivesmentioning
confidence: 99%
“…Positive relationship is established between dividend payout and profitability, asset tangibility among Jordanian firms (Basil, 2011). Profitable, mature, and liquid Indian firms have higher dividend payout ratio (Labhane & Mahakud, 2016). Dividend payout among Indian firms have been on decline due to the dividend payout policies of smaller, less profitable, and younger firms (Labhane, 2017).…”
Section: Theoretical Postulatesmentioning
confidence: 99%
“…Tax variables were proxied by some studies (Brennan, 1970;DeAngelo & Masulis, 1980). Liquidity is proxied by current ratio (Labhane & Mahakud, 2016) along with other measures of liquidity. Tangibility measures include ratios like fixed assets divided by total assets (Titman & Wessels, 1988).…”
Section: Variable Selectionmentioning
confidence: 99%
“…Analysing the determinants of the dividend policy of Indian listed companies, Labhane and Mahakud (2016) revealed that firms that were larger, more profitable, more mature and highly liquefied have higher dividend payout ratios. In contrast, firms with high investment opportunity, financial leverage, and business risks, have lower dividend payout ratios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although generally limited, the investigation of firms' dividend payment decisions in an emerging capital market like India have been done before (see Mahapatra & Sahu, 1993;Bhat & Pandey, 1994;Baker & Kapoor, 2015;Labhane & Mahakud, 2016). However, these studies have not explored the impact of catering incentives on dividend payment decisions specifically.…”
Section: Introductionmentioning
confidence: 99%